PENINGKATAN AKTIVITAS DAN HASIL BELAJAR BIOLOGI MELALUI PENERAPAN STRATEGI PQ4R (PREVIEW, QUESTION, READ, REFLECT, RECITE, AND REVIEW) - Hidayathuz Zahra (Bioedukasi Jurnal Pendidikan Biologi, 2013)
Students achievement in Biology Class XI IPA1 SMA Muhammadiyah 1 Metro is still low, in learning process students participant is low so learning process is not active. From that coundition the researcher aplly PQ4R Strategy (Preview, Question, Read, Relfect, Recite, and Review). This strategy can help students to remember in reading comprehension, asking question and answering question that given by the teacher. In this reseach is Class Room Active Reseach (CAR). This reseach is purpose to increase the activity and students result of the study of XI IPA1 SMA Muhammadiyah 1 Metro. Data of students activities in the class are: students who give attention to the teacher explanation is 87,7%, reading activity is 81,5%, asking question activity 21%, doing an examination is 84,2%, and activity make outhine is 75,4%. The result study of the students in Pra-CAR in cycle II is increasing to be 24,5%, on the Pra-CAR 46,5% to be 71%. While the increasing of cycle I to cycle II is 58% from cycle I from 13% to be 71% to cycle II.A.Kata kunci: PQ4R aktivitas belajar, hasil belajar